Design and Implementation of P300 Brain-Controlled Wheelchair with a Developed Wireless DA Converter - Li, Zizhu; Li, Boning; Luo, Wenping; Cao, Jianting (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2023)
This article presents a P300 brain-controlled wheelchair system utilizing a wireless Digital-to-Analog converter for signal transmission. The wireless Digital-to-Analog converter addresses issues with device connectivity and simplifies signal transmission, removing the need for complex serial port protocols. A support vector machine model is trained to extract the P300 component from the Electroencephalogram signal. A P300 stimulator is designed to elicit the P300 component response, with subjects controlling the wheelchair's movement by looking at randomly flickering white circles. Experimental validation is conducted on a modified wheelchair, demonstrating the effectiveness and reliability of the proposed method.